Performing Postracialism Reflections on Antiblackness, Nation, and Education through Contemporary Blackface in Canada - Howard, Philip S.S (University of Toronto Press, 2023)
Blackface - instances in which non-Black persons temporarily darken their skin with make-up to impersonate Black people, usually for fun, and frequently in educational contexts - constitutes a postracialist pedagogy that propagates antiblack logics. In Performing Postracialism, Philip S.S. Howard examines instances of contemporary blackface in Canada and argues that it is more than a simple matter of racial (mis)representation. The book looks at the ostensible humour and dominant conversations around blackface, arguing that they are manifestations of the particular formations of antiblackness in the Canadian nation state and its educational institutions. It posits that the occurrence of blackface in universities is not incidental, and outlines how educational institutions' responses to blackface in Canada rely upon a motivation to protect whiteness. Performing Postracialism draws from focus groups and individual interviews conducted with university students, faculty, administrators, and Black student associations, along with online articles about blackface, to provide the basis for a nuanced examination of the ways that blackface is experienced by Black persons. The book investigates the work done by Black students, faculty, and staff at universities to challenge blackface and the broader campus climate of antiblackness that generates it.